Analysis of BrewDog's Competitive Strategy Against Major Beer Companies (aSSIST Business Review, 2025)
This study conducts an in-depth analysis of BrewDog's success story—a small craft beer company that grew into a global brand—using the SER-M model. BrewDog transformed the craft beer market landscape through innovative marketing, a distinctive brand image, and a user-centric approach. This study analyzes BrewDog's success factors from the perspectives of the subject (leadership and capabilities), environment (market trends), resources (brand and community), and mechanism (marketing and strategy), identifying the success mechanism that operated through their interactions.From its inception, BrewDog captured market attention with unconventional products and viral marketing. For instance, Punk IPA secured a 40% sales share in the UK craft beer market in 2022, establishing itself as the brand's flagship product (Osum, 2024). The Equity for Punks crowdfunding campaign raised over £100 million and built a community of 200,000 investors (BrewDog, 2022). This success resulted from innovative leadership, the growth of the craft beer market, shifting consumer trends, and a social media-centric marketing mechanism.BrewDog now seeks growth potential through sustainability initiatives, pub network expansion, and global market entry. Achieving carbon neutrality certification in 2020 increased preference among environmentally conscious consumers by 15% (OppGenetix, 2024). This study provides practical insights for SMEs to develop differentiation strategies when competing against large corporations, using BrewDog as a case study. Notably, collaboration with local communities serves as a key strategy to enhance innovation and sustainability (Choi, K. & Cho, D. S., 2023:983).This study proceeds in the following order: theoretical background of the SER-M model, analysis of BrewDog and its competitors, explanation of success mechanisms, and presentation of practical and academic implications. It explores how innovative competitive strategies for late entrants in traditional industries and user-centered design contribute to corporate success.
Keywords: Craft Beer Industry; BrewDog; SER-M Model; Competitive Mechanism